Essential oils as capsule disruptors: enhancing antibiotic efficacy against multidrug-resistant Klebsiella pneumoniae - El-Demerdash, Azza SalahEldin; Alfaraj, Rihaf; Farid, Faten A.; Yassin, Mohamed H.; Saleh, Abdulrahman M.; Dawwam, Ghada E. (Frontiers in Microbiology, 2024)
The study investigated the antibacterial activity and synergistic effects of effective essential oils in combination with the drug of choice against multidrug-resistant Klebsiella pneumoniae (MDR-KP), a significant pathogen causing severe infections with high mortality rates. K. pneumoniae was isolated from both human and animal sources, with a prevalence rate of 25%, predominantly from human samples. Tea tree and thyme essential oils exhibited strong antibacterial activity, with inhibition zones ranging from 14 to 32 mm. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values confirmed their potency. Checkerboard assays confirmed synergistic effects of these essential oil-amikacin combinations against most isolates. Notably, these combinations significantly downregulated the expression of key capsule virulence genes (wcaG, rmpA, magA, uge, and wabG), suggesting a novel mechanism for enhancing amikacin efficacy. Transmission electron microscopy revealed disrupted cell integrity in MDR-KP cells treated with the combinations. Molecular docking analysis identified Terpinen-4-ol, Farnesol, 1,4-Dihydroxy-p-menth-2-ene, and 7-Oxabicyclo [4.1.0] heptane as potential bioactive compounds responsible for the observed effects. By effectively combating MDR-KP, this research holds promise for reducing antibiotic resistance, improving treatment outcomes, and ultimately enhancing potential care.